A Qualitative Analysis of the Impediments to Business Innovation and Information Management in Nigeria: A Policy Stance - Adewole, Ololade Grace; Okrigwe, Festa Ndutimi; Opele, Jacob Kehinde; Omotoso, Kehinde Oluwaseun (International Journal of Business, Economics and Management, 2020)
The ability of the Nigerian business sector to actively engage in innovative activities is germane to sustainable national growth and development. While the government has the primary responsibility to formulate policies that can mitigate societal problems and sustain economic stability, the business sector in the country has continued to experience government failure to implement previously formulated policies. The current study attempted to investigate the impediments to Nigerian Business Innovation and Information Management through the lens of a qualitative approach. The authors conducted a guided oral interview through the WhatsApp platform which was created to gather all impediments to the survey from the field officers who took an active part in data collection in six geopolitical zones in Nigeria. Subsequently, data gathered was analysed through Atlas. Ti version 8 software and the findings were presented by the regional spread. The study revealed that there are benefits in conducting a national business innovation survey, and these include input into effective planning, formulation, and implementation of relevant policies for sustainable development in the country. The outcome of the survey helps to benchmark the results with what obtains in other African countries. Key impediments include the firm's unwillingness to declare turnover because of the fear of an increase in tax policy and poor collaboration between the government and the industry. It was recommended that the government should come up with policies that will encourage business activities in the country and improve the relationship between the government and the industry.